Brief version of the CAMCOG for illiterate older adults with Alzheimer’s dementia - Cecato, Juliana Francisca; Balduino, Everton; Martinelli, José Eduardo; Aprahamian, Ivan (Arquivos de Neuro-Psiquiatria, 2021)
Background: The Cambridge Cognition Examination (CAMCOG) is one of the most used cognitive assessment batteries for older adults. Objective: To evaluate a brief version of the CAMCOG for illiterate older adults (CAMCOG-BILL) with Alzheimer’s dementia (AD) and healthy controls (CG). Methods: Cross-sectional case-control study with 246 illiterate older adults (AD [n=159] and CG [n=87], composed by healthy seniors without cognitive complaints) who never attended school or took reading or writing lessons. Diagnosis of AD was established based on the NIA-AA and DSM-5 criteria. All participants were assessed with the CAMCOG by a researcher blinded for diagnosis. To assess the consistency of the chosen CAMCOG-BILL sub-items, we performed a binary logistic regression analysis. Results: Both the CAMCOG and the CAMCOG-BILL had satisfactory psychometric properties. The area under the curve (AUC) was 0.932 (p<0.001) for the original version of CAMCOG and 0.936 for the CAMCOG-BILL. Using a cut-off score of ≥60 (CAMCOG) and ≥44 (CAMCOG-BILL), both instruments had the same sensitivity and specificity (89 and 96%, respectively). Conclusion: The CAMCOG-BILL may be a preferred tool because of the reduced test burden for this vulnerable subgroup of illiterate patients with dementia.
Keywords: Alzheimer Disease; Education; Neuropsychological Tests; Aging